Developing A Digital-Based Library To Enhance Educational Knowledge Among Students - Rizky, Muhammad Al; Hartati, Hartati; Syafaruddin, Syafaruddin (Department of Physical Education, Sport, Health and Recreation, 2024)
This Education serves as a means or pathway for individuals to unlock and develop their potential through the learning experiences they acquire. A type of learning resource is the digital library, which represents an innovative facet of library advancement designed to engage a broader audience. This study emerged from the absence of e-books or digital resources for high school students, specifically those at State Vocational High School 2 Palembang. The research follows a developmental approach using the Research and Development (R&D) method. The study employs two types of instruments: a product validity sheet addressed to both media and material experts, and an instrument evaluating practicality and effectiveness aimed at students, particularly those in class X at State Vocational High School 2 Palembang. The research yields a Digital Library Website for Physical Education, Sports, and Health subjects, deemed suitable as a learning resource based on validation results. Material experts assigned an average score of 4.4, categorizing it as